Research on determinants of IPO underpricing: Evidence from China - SONG, Jia (2020)
IPO underpricing refers to the phenomenon that the IPO price in the primary market is significantly lower than the initial transaction price in the secondary market, resulting in a higher risk-free excess return. China's IPO underpricing phenomenon is quite prominent, which reduces the efficiency of resource allocation in the stock market. Based on the existing literature and unique features of China’s stock market, this paper uses Bloomberg and Eastmoney database to obtain the IPO data of the Chinese A-share market from January 2014 to December 2019, and it establishes a multiple regression model to make an empirical study on the underpricing phenomenon of Chinese IPO and its influencing factors. The regression results show that offering size, offering price, time interval, lot winning rate, turnover rate, and earnings per share have significant effects on the degree of underpricing of new shares. Finally, on the basis of the analysis and discussion of the empirical results, this dissertation provides suggestions to the regulatory authorities, the IPO participants, and investors.